KARAKTERISTIK FISIKOKIMIA TEPUNG TEMPE KECAMBAH KEDELAI - Astawan, Made; Wresdiyati, Tutik; Ichsan, Muhammad (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
This research was conducted to compare physicochemical characteristics of germinated soybean tempe flour (GST flour) and soybean tempe flour (ST flour). Soybean was germinated within 28 hours and then processed into tempe. Germinated soybean tempe and soybean tempe were freeze-dried for 26 hours, and then milled into GST flour and ST flour. The GST flour and ST flour were used for physical and chemical analysis. The used of germinated soybean was proven to affect the quality of flour. GST flour had 53.37 % db protein, 24.97 mg AEAC antioxidant capacity/100 g tempe, 5.08 mg tocopherol/100 g db, 81.75 mg isoflavone/100 g db, and minerals (Ca, P, Fe, Zn) which were higher than that of the ST flour. GST flour also had better quality than that of ST flour, in term of: higher bulk density (0.42 g/ml), lower water activity (0.63), and lower repose angle (39.94o).Keywords: chemical characteristic, germinated soybean tempe, physical characteristic, soybean tempe